The Role of Commissioners and Audit Committee to Firm Value Mediated by Risk Management Disclosures - Agris Haryanto Prakasa; Yanuar Ramadhan (AFRE (Accounting and Financial Review), 2023)
This research originated from the phenomenon of competition that occurred between public companies listed on the Indonesia Stock Exchange (IDX). The intense competition that occurred encouraged each company to be adaptive to changes in the economic situation that often changed. 56 samples of Indonesian public companies were selected based on their presence on the IDX, which operates in the property and real estate sector in 2019-2021. The background for choosing this sector is because the property and real estate sector experienced a contraction in stock prices during 2021 to 2023. This research uses 56 companies as samples and a 3-year observation period, resulting in 168 data that became the source of data for this study. This study obtained results that the size of the board of commissioners and audit committee partially influenced the risk management information disclosed by the company. Positive results were obtained for the size of the board of commissioners and risk management disclosure partially affecting firm value. The presence of risk management disclosure was able to mediate the indirect relationship between the board of commissioners and firm value. Meanwhile, the audit committee does not affect the firm value either directly or indirectly.DOI: https://doi.org/10.26905/afr.v6i3.10506